Giant gastric schwannoma presenting with upper gastrointestinal bleeding - Hakan ŞENTÜRK; Abdullah SONSUZ; Cihan URA MD; Süha GÖKSAL MD; Sebati ÖZDEMİR and Ahsev BALIC MD and Perihan AKIN (Turkish Journal of Gastroenterology, 2019)
-